Changes in pregnancy outcomes during the COVID-19 lockdown in Iran - Fahimeh Ranjbar; Leila Allahqoli; Soheila Ahmadi; Robab Mousavi; Maryam Gharacheh; Nooshin Eshraghi; Ibrahim Alkatout (BMC, 2021)
Abstract Background The Covid-19 pandemic response is influencing maternal and neonatal health care services especially in developing countries. However, the indirect effects of Covid-19 on pregnancy outcomes remain unknown. The aim of the present study was to compare pregnancy outcomes before and after the beginning of the Covid-19 pandemic in Iran. Methods We performed a retrospective analysis of the medical records of 2,503 pregnant women with singleton pregnancies, admitted to the maternity department of a women's hospital in Tehran, Iran, during the pre-Covid-19 pandemic (February 19 to April 19, 2019) and the intra-Covid- 19 pandemic (February 19 to April 19, 2020) period. Results We included 2,503 women admitted to the hospital; 1,287 (51.4 %) were admitted before the Covid-19 lockdown and 1,216 (48.6 %) during the Covid-19 lockdown. There were no significant differences in stillbirth rates (p = 0.584) or pregnancy complications (including preeclampsia, pregnancy-induced hypertension and gestational diabetes) (p = 0.115) between pregnant women in the pre- and intra-pandemic periods. However, decreases in preterm births (p = 0.001), and low birth weight (p = 0.005) were observed in the pandemic period compared to the pre-pandemic period. No significant difference in the mode of delivery, and no maternal deaths were observed during the two time periods. Conclusions In our study we observed a decrease in preterm births and low birth weight, no change in stillbirths, and a rise in the admission rates of mothers to the ICU during the initial Covid-19 lockdown period compared to pre-Covid-19 lockdown period. Further research will be needed to devise plan for immediate post-pandemic care and future health care crises.